Changing perspectives in political economy - Renate Mayntz (Max Planck Institute for the Study of Societies, 2019)
The history of a research field called political economy dates back to the eighteenth century, giving rise to a variety of disciplinary approaches, and experienced a renaissance as a multidisciplinary field after the Second World War, combining economic, political science, and sociological approaches. The divergence between economic globalization and the nationally restricted scope of economic policy directs interest to the relationship between politics and the economy. A quantitative analysis of the articles published in two dedicated political economy journals shows major trends of the developing research field. The relationship between politics and economy is interpreted rather widely, and research is largely focused on Western capitalist nations. In conclusion, two avenues for further research in the field are briefly discussed. – – Die Geschichte eines Forschungsfelds unter der Bezeichnung "politische Ökonomie" geht ins 18. Jahrhundert zurück und führte in der Folgezeit zu unterschiedlichen disziplinären Schulen. Nach dem Zweiten Weltkrieg erlebte die politische Ökonomie eine erstaunliche Renaissance als ein multidisziplinäres Forschungsfeld. Widersprüche zwischen ökonomischer Globalisierung und einer national eingehegten Rolle von Wirtschaftspolitik lenkten das Interesse auf die Wechselbeziehungen zwischen Politik und Ökonomie. Eine quantitative Analyse der in zwei neueren Zeitschriften publizierten Aufsätze zeigt Schwerpunkte der Analyse; die Beziehung zwischen Politik und Ökonomie wird sehr differenziert gesehen und kapitalistische westliche Nationen bilden den Schwerpunkt der Forschung. Abschließend wird auf zwei wichtige Fragen für die Forschung hingewiesen.
hdl:21.11116/0000-0004-5AA4-E
Keywords: 300; capitalism; history of political economy; relationship politics/economy; Western capitalist nations; Geschichte der politischen Ökonomie; Kapitalismus; Verhältnis Politik/Ökonomie; westliche kapitalistische Nationen